2003
DOI: 10.1021/ja034820y
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Determine the Protein Resistance of Oligoether Self-Assembled Monolayers − Internal Hydrophilicity, Terminal Hydrophilicity, and Lateral Packing Density

Abstract: Protein resistance of oligoether self-assembled monolayers (SAMs) on gold and silver surfaces has been investigated systematically to elucidate structural factors that determine whether a SAM will be able to resist protein adsorption. Oligo(ethylene glycol) (OEG)-, oligo(propylene glycol)-, and oligo(trimethylene glycol)-terminated alkanethiols with different chain lengths and alkyl termination were synthesized as monolayer constituents. The packing density and chemical composition of the SAMs were examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
702
5
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 660 publications
(763 citation statements)
references
References 44 publications
(80 reference statements)
55
702
5
1
Order By: Relevance
“…A similar observation has been made by the Grunze group, who found that surfaces with similar wettability can show different settlement of zoospores [33,82]. In this study, ethylene glycols with different chain length and thus decreasing packing density were used [82,83]. Monte Carlo simulations revealed that such a decreased packing density facilitates penetration of water into the thin films, providing the necessary steric freedom for a stable binding of water [84,85].…”
Section: Surface Cues Can Trigger Permanent Adhesion Of Zoospores Of supporting
confidence: 76%
See 2 more Smart Citations
“…A similar observation has been made by the Grunze group, who found that surfaces with similar wettability can show different settlement of zoospores [33,82]. In this study, ethylene glycols with different chain length and thus decreasing packing density were used [82,83]. Monte Carlo simulations revealed that such a decreased packing density facilitates penetration of water into the thin films, providing the necessary steric freedom for a stable binding of water [84,85].…”
Section: Surface Cues Can Trigger Permanent Adhesion Of Zoospores Of supporting
confidence: 76%
“…Monte Carlo simulations revealed that such a decreased packing density facilitates penetration of water into the thin films, providing the necessary steric freedom for a stable binding of water [84,85]. Despite the different hydration, all of the tested surfaces have a similar water contact angle [82,83]. Ulva zoospore experiments show that spores adhere much weaker on well hydrated surfaces [33], an observation in line with the protein resistance of the surfaces [83].…”
Section: Surface Cues Can Trigger Permanent Adhesion Of Zoospores Of mentioning
confidence: 56%
See 1 more Smart Citation
“…(ZP=-46.9 mV) [140]. Microorganisms are negatively charged over a large pH range (Figure 10(a)), and in natural sea water (pH 7-8) will carry a negative charge [142]. As a result, electrostatic interaction between cells and metal cations promotes the adhesion process.…”
Section: Antifouling By Changing the Zeta Potentialmentioning
confidence: 99%
“…When chemical grafting is concerned instead of coating, oligomers of ethylene oxide (chains containing 3 to 9 EO units) are also efficient [18][19][20]. Surface treatment of glass and metal oxides is generally performed with commercial silane derivatives, such as 3-[methoxy (polyethyleneoxy)] propyl trimethoxysilane or trichlorosilane ( Fig.…”
Section: Design and Synthesis Of The Organic Reagentmentioning
confidence: 99%